Partially redundant enhancers cooperatively maintain Mammalian Pomc expression above a critical functional threshold - Lam, Daniel D. (2015)
Cell-specific expression of many genes is conveyed by multiple enhancers, with each individual enhancer controlling a particular expression domain. In contrast, multiple enhancers drive similar expression patterns of some genes involved in embryonic development, suggesting regulatory redundancy. Work in Drosophila has indicated that functionally overlapping enhancers canalize development by buffering gene expression against environmental and genetic disturbances. However, little is known about regulatory redundancy in vertebrates and in genes mainly expressed during adulthood. Here we study nPE1 and nPE2, two phylogenetically conserved mammalian enhancers that drive expression of the proopiomelanocortin gene (Pomc) to the same set of hypothalamic neurons. The simultaneous deletion of both enhancers abolished Pomc expression at all ages and induced a profound metabolic dysfunction including early-onset extreme obesity. Targeted inactivation of either nPE1 or nPE2 led to very low levels of Pomc expression during early embryonic development indicating that both enhancers function synergistically. In adult mice, however, Pomc expression is controlled additively by both enhancers, with nPE1 being responsible for ∼80% and nPE2 for ∼20% of Pomc transcription. Consequently, nPE1 knockout mice exhibit mild obesity whereas nPE2-deficient mice maintain a normal body weight. These results suggest that nPE2-driven Pomc expression is compensated by nPE1 at later stages of development, essentially rescuing the earlier phenotype of nPE2 deficiency. Together, these results reveal that cooperative interactions between the enhancers confer robustness of Pomc expression against gene regulatory disturbances and preclude deleterious metabolic phenotypes caused by Pomc deficiency in adulthood. Thus, our study demonstrates that enhancer redundancy can be used by genes that control adult physiology in mammals and underlines the potential significance of regulatory sequence mutations in common diseases.